2013
DOI: 10.1080/15287394.2013.845865
|View full text |Cite
|
Sign up to set email alerts
|

Burrowing in the Freshwater MusselElliptio complanatais Sexually Dimorphic and Feminized by Low Levels of Atrazine

Abstract: The widely used herbicide atrazine (ATR) may have endocrine-associated adverse effects, including on behavior. In this study, 120 adult freshwater mussels, Elliptio complanata, were exposed to ATR at the environmentally-relevant concentrations of 1.5, 15, or 150 μg/L. Burrowing depth was evaluated hourly for 6 hr and at sacrifice animals were sexed by gonad smear. Female controls burrowed overall approximately 30% less than males, the first report of sexual dimorphism in this behavior. Atrazine at 15 μg/L femi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Our findings are similar to those of Quinn et al [41], who reported vitellogenin induction in both sexes of freshwater mussels (Dreissena polymorpha) after exposure to municipal effluents containing a mixture of endocrine-disrupting chemicals including BPA. Vitellin-like proteins' induction was also observed in both sexes of organisms exposed to ATZ at concentrations 10-fold higher than environmental levels, confirming the observations of Flynn et al [42] with the freshwater mussel, Elliptio complanata, exposed to ATZ at 1.5 mg/L. The mechanisms by which BPA disturbs invertebrate reproductive and endocrine systems remain unknown [43], but the poor ability of male mussels to clear vitellin-like protein could lead to an accumulation to concentrations that have adverse health effects and may ultimately compromise their reproduction or lead to a higher incidence of hermaphroditism in exposed populations.…”
supporting
confidence: 87%
“…Our findings are similar to those of Quinn et al [41], who reported vitellogenin induction in both sexes of freshwater mussels (Dreissena polymorpha) after exposure to municipal effluents containing a mixture of endocrine-disrupting chemicals including BPA. Vitellin-like proteins' induction was also observed in both sexes of organisms exposed to ATZ at concentrations 10-fold higher than environmental levels, confirming the observations of Flynn et al [42] with the freshwater mussel, Elliptio complanata, exposed to ATZ at 1.5 mg/L. The mechanisms by which BPA disturbs invertebrate reproductive and endocrine systems remain unknown [43], but the poor ability of male mussels to clear vitellin-like protein could lead to an accumulation to concentrations that have adverse health effects and may ultimately compromise their reproduction or lead to a higher incidence of hermaphroditism in exposed populations.…”
supporting
confidence: 87%
“…2008 ; Zieritz and Aldridge 2011 ; Haag 2012 ). Interestingly, sexual dimorphism in burrowing behavior has also been reported in the freshwater mussel DUI species Elliptio complanata ( Flynn et al. 2013 ).…”
Section: Resultsmentioning
confidence: 76%
“…In our case, we used this modeling approach to describe intensity of burrowing and movement following TCS exposure. This approach to analyzing mussel behavioral data is appropriate because some individuals did not conduct behaviors during the study duration and therefore the data are considered right-censored, which the proportional hazard model accommodates (see Waller et al, 1999;Hazelton et al, 2014); the alternative approach is to remove non-responding individuals from the dataset and use a group means statistical test (e.g., Flynn et al, 2013). The parameter estimates are generated as a proportional likelihood of an event occurring relative to the control group.…”
Section: Discussionmentioning
confidence: 99%